Understanding the Role of Gender Diversity in Leadership: A Qualitative Analysis - Eri Kusnanto; Ngadi Permana; Muhammad Rizal (International Journal of Business, Marketing, Economics & Leadership (IJBMEL), 2024)
This qualitative study aims to explore the significance of gender diversity in leadership roles. Employing a qualitative research design, the study utilizes purposive sampling to select participants from various organizational contexts. Semi-structured interviews are conducted to gather in-depth insights into participants' perceptions and experiences regarding gender diversity in leadership. Thematic analysis is employed to identify patterns, themes, and meanings within the data. The findings reveal nuanced perspectives on the impact of gender diversity on leadership effectiveness, organizational culture, and decision-making processes. This study contributes to the existing literature by offering rich qualitative insights into the complex dynamics of gender diversity in leadership roles.